Cultural Heritage Damage and Post-Disaster Recovery Under Compound Hazards: The Noto Peninsula Earthquake of January 1, 2024 Followed by Extreme Rainfall (Journal of Science and Engineering, 2026)
A devastating earthquake hit the Noto Peninsula in Japan on the first day of 2024, a region rich in history, culture and nature, caused serious damage to those heritages. The present paper introduces the earthquake damage to cultural heritages together with the damage related to outlines of the major earthquake. Recovery of the damaged cultural heritages started on the basis of the disaster prevention measures that had been developed since the Kobe Earthquake in 1995. However, during the process of recovery phase, the earthquake-affected areas in the Noto Peninsula suffered further damage from the disastrous rainfall in September, 2024. In the present paper, the earthquake damage to the cultural heritages are reviewed with being followed by the further damage caused by the heavy rainfall in order to share our experience internationally.